2017
DOI: 10.3390/e19060261
|View full text |Cite
|
Sign up to set email alerts
|

Spurious Results of Fluctuation Analysis Techniques in Magnitude and Sign Correlations

Abstract: Fluctuation Analysis (FA) and specially Detrended Fluctuation Analysis (DFA) are techniques commonly used to quantify correlations and scaling properties of complex time series such as the observable outputs of great variety of dynamical systems, from Economics to Physiology. Often, such correlated time series are analyzed using the magnitude and sign decomposition, i.e., by using FA or DFA to study separately the sign and the magnitude series obtained from the original signal. This approach allows for disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…SampEn also needs three input parameters, N , m, and a threshold r, but it is much more sensitive to these input values than PE, since a suboptimal choice of these values can lead to incorrect results [28]. DFA is also quite unstable when the input parameters change [29]. This is a complete new approach to the analysis of blood glucose time series, where most of the methods have been based on DFA [30,31] or Sample Entropy (Multiscale) [32,33,21].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…SampEn also needs three input parameters, N , m, and a threshold r, but it is much more sensitive to these input values than PE, since a suboptimal choice of these values can lead to incorrect results [28]. DFA is also quite unstable when the input parameters change [29]. This is a complete new approach to the analysis of blood glucose time series, where most of the methods have been based on DFA [30,31] or Sample Entropy (Multiscale) [32,33,21].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…In this article, we apply the horizontal visibility graph algorithm to map fractal and multifratal time series into graphs. By investigating topological characteristics of the resulting graphs, we first show that this approach can well detect linear and nonlinear correlations, even for situations that DFA and MFDFA predict uncorrelatedness, due to some technical issues [23,29,30]. On the other hand, we show that owing to the unique characterisitc of the horizontal visibility graph algorithm, one can calculate linear or nonlinear correlations, without the need to eliminate the impact of non-Gaussianity of the original series.…”
Section: Introductionmentioning
confidence: 94%
“…In DFA and MFDFA techniques, one usually confronts with some challenges such as choosing an appropriate polynomial order for detrending procedure, finding a proper scaling region, and detecting correct correlations that can be affected by the probability distribution function (PDF) of the series. Recently, it has been shown that in some conditions, DFA and MFDFA are not able to extract correct scaling behaviors of a time series [23,29,30]. The existence of crossovers in the scaling behavior at some particular scale s c along with the q dependency of that s c are two examples of possible inaccuracy in the multifractal spectrum estimation.…”
Section: Introductionmentioning
confidence: 99%
“…FFM has become the standard method to create a controlled power-law correlated time series, and it is used in many contexts for that purpose [ 21 , 22 , 23 , 24 , 25 , 26 ]…”
Section: Detrended Fluctuation Analysis and Autocorrelation Function In Time Series With Power–law Correlationsmentioning
confidence: 99%